2021
DOI: 10.3390/ijerph182413098
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Attitudes toward COVID-19 Passports: Evidences from Spain

Abstract: A so-called COVID-19 passport or Immunity passport (IP) has been proposed to facilitate the mobility of individuals while the SARS-CoV-2 pandemic persists. A COVID-19 passport can play a key role in the control of the pandemic, specifically in areas with a high density of population, and the help of smart city technology could be very useful to successfully implement IPs. This research studies the impact of ethical judgments on user attitudes toward using vaccine passports based on a Multidimensional Ethics Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Hence, the question of who opposes the adoption of CVCs (analogous to which groups are vaccine hesitant [ 14 ]) may have more policy relevance. Existing studies exploring public perception of CVCs have found mixed opinions [ [15] , [16] , [17] , [18] , [19] , [20] ]. However, the majority of these studies have been western-centric, and their findings may not be generalisable to Asia given contextual differences such as vaccination rates, trust in government, tolerance for and adherence to restrictive COVID-19 policies, dependency on tourism among others [ 12 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the question of who opposes the adoption of CVCs (analogous to which groups are vaccine hesitant [ 14 ]) may have more policy relevance. Existing studies exploring public perception of CVCs have found mixed opinions [ [15] , [16] , [17] , [18] , [19] , [20] ]. However, the majority of these studies have been western-centric, and their findings may not be generalisable to Asia given contextual differences such as vaccination rates, trust in government, tolerance for and adherence to restrictive COVID-19 policies, dependency on tourism among others [ 12 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coverage is the ratio of cases that, presenting the results, are explained by the solution. The coverage of a solution measures the ability of the recipe to explain all of the observations and can be assimilated to R 2 [ 70 ]. Coverage is the parameter that explains the empirical relevance of the solution.…”
Section: Resultsmentioning
confidence: 99%
“…To establish the individual net effects, a multiple linear regression was performed, in which OVE was explained on the basis of INF, SIM, MAT, SEF and INNThe significance of the regression coefficients evaluated with Student’s t -test and the overall goodness of the regression model with R 2 [ 70 ]. This regression has an adjusted coefficient of determination of 0.999.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides key insights for Eastern Europe, which is understudied on this critical policy and public health topic. The focus of most international research and the global media has often focused primarily on outcomes of Western countries and associated factors – especially the resistance toward vaccination and public health measures (18) – pandemic outcomes have been poorer in Eastern Europe than Western counterparts. In the early phases of the pandemic, urgent short term measures were effective in preventing deaths in Eastern Europe (19), but over the longer term, other factors have played a more important role in mitigating the pandemic.…”
Section: Discussionmentioning
confidence: 99%